2019
DOI: 10.7567/1882-0786/ab2a1b
|View full text |Cite
|
Sign up to set email alerts
|

First-principles insight on the electronic and optical properties of Ge-based inorganic perovskites

Abstract: Using density functional theory calculations, we explore the structural stability, electronic and optical properties of inorganic Ge-based halide perovskites Cs1-xRbxGeI3. The calculated results indicate that the band gap gradually decreases when the proportion of Rb increases. The band gap of RbGeI3 is predicted to be 1.45 eV. The formation energy and elastic constants indicate that Cs1-xRbxGeI3 perovskites can be synthesized under the suitable method. These Ge-based inorganic perovskites can be used as an li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…For exploring their potential application in PV, the bandgap assessment for compositional variation supports the use of fully inorganic lead‐free Cs 1− y Rb y Ge(Br x I 1− x ) 3 compositions. [ 41–48 ]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For exploring their potential application in PV, the bandgap assessment for compositional variation supports the use of fully inorganic lead‐free Cs 1− y Rb y Ge(Br x I 1− x ) 3 compositions. [ 41–48 ]…”
Section: Methodsmentioning
confidence: 99%
“…For exploring their potential application in PV, the bandgap assessment for compositional variation supports the use of fully inorganic leadfree Cs 1Ày Rb y Ge(Br x I 1Àx ) 3 compositions. [41][42][43][44][45][46][47][48] Based upon the optimal bandgap, it will be suitable to further explore CsGe(Br x I 1Àx ) 3 and Cs 1Àx Rb x GeI 3 , instead of a complex Cs 1Ày Rb y Ge(Br x I 1Àx ) 3 . The crystal structure of CsGeI 6d.…”
Section: Simulation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study [20], CsSnI 3 is reported to have a direct energy bandgap (1.3 eV) and mobility as 400 cm −2 /Vs. However, very few studies are available for Rb-based inorganic perovskites [21][22][23][24].…”
mentioning
confidence: 99%